Polyoxometalates crystal growth, crystal structure, characterization and photocatalytic activities - Ren, Jie (2013)
The application of using polyoxometalates (POMs in short) as a catalyst to directionally control the organic reactions becomes widespread. For this final year project, the target is to understand the Keggin structure of polyoxometalates. By using the simple oxysalts dehydration under certain pH method to synthesis the analysis subjects H4[PMo11VO40].32H2O, H5[PMo10V2O40].34H2O, and H6[PMo9V3O40].34H2O. Experiments also showed that under different amount of precursor added for reaction, the number of Vanadium replacement of Molybdenum is one, two, and three respectively comparing with the simplest homo-POM H3PMo12O40. X-ray diffraction, Infrared spectra were obtained to verify the correct chemical position and functional groups. The synthesized chemicals were controlled to form micellar POMs and applied for catalysis the wet air oxidation of phenol under ambient conditions. The phenol solution is taken out at 25 minutes interval for 100 minutes and using the centrifuge procedure to get the oxide solution respectively. The UV spectra is applied to measure the amount of phenol reacted and hence calculated the efficiency of synthesized POMs as a catalyzer in phenol oxidation reaction.